The myth of the artist – from birth to collapse: notes on the Lithuanian present-day novel (Colloquia Comparativa Litterarum, 2025)
The article, based on the comparative principle, seeks to introduce to a wide audience two novels by Lithuanian writers Kęstutis Navakas (Vyno kopija [“The Wine Copy”], 2016) and Marius Ivaškevičius (Tomas Mūras, 2022), whose authors wish to reflect on the status of the artist in the current era of excess and prosperity. The myth of the artist began taking shape in the 19th century and remained at its height throughout the 20th century, even though art itself underwent many changes. Is the artist still the representative of the elite in society in a postmodern age, when the line between art and pop, between personality and promotional image, is almost blurred? These are the questions the authors ask and try to answer, joining inevitably those European writers who placed the creative person at the centre of their fictional world over the last two centuries. Anyone who writes on this subject almost inevitably becomes an author of World Literature, as we have understood it since Goethe. The study seeks to reveal the diversity of literary associations, sometimes unconsciously touched upon by the authors, and the tradition of the European novel in dealing with questions of art, man, and his meaning on Earth.